Comparison of Efficacy and Safety of First-Line Treatment Options for Unresectable Stage III Non-Small Cell Lung Cancer: A Retrospective Analysis - Luqing Zhao; Zhiting Zhao; Xiaoqi Yan; Fei Wu; Ning Sun; Renhong Guo; Shaorong Yu; Xiao Hu; Jifeng Feng (International Journal of Clinical Practice)
Background. Based on PACIFIC trial, durvalumab as consolidation therapy following concurrent chemoradiotherapy (cCRT) has been a new standard treatment for unresectable stage III non-small cell lung cancer (NSCLC). In clinical applications, there are heterogeneous adjustments or novel strategies following specialized discussions in experienced multidisciplinary teams. This study retrospectively compared the efficacy and safety of different first-line treatments for unresectable stage III NSCLC. Methods. We retrospectively analyzed 397 patients who received first-line treatment for unresectable stage III NSCLC. Comparisons and statistical analyses of treatment were made in terms of efficacy and safety. Adverse events and responses were assessed using CTCAE v5.0 and RECIST v1.1. The progression-free survival (PFS) was estimated using the Kaplan–Meier method or the Cox survival regression model and compared using the log-rank test. Results. In wild-type driver genes group, the objective response rate (ORR), disease control rate (DCR), and median PFS (mPFS) were prolonged in the radiotherapy group compared to those in the nonradiotherapy group (ORR: 50.94% vs. 30.06%, p < 0.001; DCR: 98.11% vs. 80.37%, p < 0.001; and mPFS: 21.00 vs. 8.20 months, p < 0.001). The incidence of pneumonia at any grade in the radiotherapy group was higher than that in the nonradiotherapy group (9.43% vs. 2.45%, p = 0.008). In the radiotherapy group, the chemoradiotherapy (CRT) plus immunotherapy subgroup had longer mPFS than the CRT subgroup, with increased toxicity at any grade (24.60 vs. 17.90 months, p = 0.025, and 83.17% vs. 65.52%, p = 0.011). In the nonradiotherapy group, the DCR and mPFS were higher in the chemotherapy plus immunotherapy subgroup than in the chemotherapy subgroup, with increased toxicity at any grade (DCR: 93.67% vs. 67.86%, p < 0.001; mPFS: 13.53 vs. 5.07 months, p < 0.001; and 68.35% vs. 41.67%, p = 0.001). In the mutant driver genes group, the efficacy did not significantly differ among the radiotherapy subgroup, targeted therapy subgroup, and radiotherapy plus targeted therapy subgroup (ORR: p = 0.633; mPFS: p = 0.450). Conclusions. For unresectable stage III NSCLC patients with wild-type driver genes, the combination of radiotherapy and immunotherapy in the initial treatment was essential to significantly improve the efficacy. For patients with mutant driver genes, radiotherapy, targeted therapy, and the combination of radiotherapy and targeted therapy showed similar short-term efficacy.